Observational Studies on the Association Between Post-diagnostic Metformin Use and Survival in Ovarian Cancer: A Systematic Review and Meta-Analysis - Gong, Ting-Ting; Wu, Qi-Jun; Lin, Bei; Ruan, Shi-Kai; Kushima, Miki; Takimoto, Masafumi (Frontiers in Oncology, 2019)
Objectives To summarize and quantify the relationship between post-diagnostic metformin use and ovarian cancer (OC) survival. Methods We systematically conducted an updated meta-analysis based on observational studies published up to December 31, 2018, identified from PubMed and Web of Science. Two team members independently extracted data and assessed the quality of each study. Summary Hazard ratios (HR) and 95% confidence intervals (CI) were calculated using a random-effects model. Results Five cohort studies including 3582 OC patients were included. All studies were graded as low risk of bias according to the Newcastle-Ottawa quality assessment scale. Post-diagnostic metformin use was associated with improved overall survival (summarized HR=0.42, 95% CI=0.31–0.56; I2=0%, P=0.842) and progression-free survival (summarized HR=0.69, 95% CI=0.45–1.07; I 2=61.9%, P=0.049) of OC patients. For OC patients with diabetes, post-diagnostic metformin use was associated with improved overall survival (summarized HR=0.51, 95% CI=0.28–0.95; I2=47.6%, P=0.149) and progression-free survival (summarized HR=0.38, 95% CI=0.27–0.55; I2=0%, P=0.594). No significant publication bias was detected in these analyses. Conclusions Post-diagnostic metformin use is consistently associated with better survival of OC patients regardless of diabetes status. Studies with larger sample sizes and prospective designs are required to confirm these findings and obtain detailed information, including standardized references for comparison, intensity and dose of metformin use, and further adjustment for potential confounders.